Lifetime Exposure to Suicide and Current Use of Suicide Prevention Competencies Among Catholic Clergy in Nigeria: A Multidimensional Structural Analysis - Oluchi Miracle Osondu; Lawrence Ejike Ugwu; Chijioke Kenneth Ayogu; Nwando Maryann Morah; Doris Chinelo Eyisi; Obinna Osita Ike; Jennifer E. Johnson; JohnBosco Chika Chukwuorji (Journal of Religion and Health, 2026)
Abstract Despite the evidence of clergy encounters with both those at risk and survivors of suicide, research examining suicide exposure and the clergy’s use of suicide prevention competencies remains limited. We examined the associations between lifetime exposure to suicide (exposure to suicidal communication, direct exposure to suicide attempts/deaths, and indirect exposure to suicide attempts/deaths) and current use of suicide prevention competencies (ministerial approaches to postvention, nonjudgmental attitude toward people affected by suicide, confidence and knowledge in talking with a suicidal person, and pastoral care with a suicidal person). We also investigated whether suicide prevention training moderates these relationships. Participants were 336 Roman Catholic priests in Nigeria who completed the Suicidal Behaviour Exposure Scale and the Measure of Suicide Prevention Clergy Competencies, including an indicator assessing whether participants had received any formal training. Results showed that lifetime exposure to suicide was associated with the use of suicide prevention competencies among priests without formal suicide prevention training, but not among those with training. The observed moderation effect was more nuanced when we examined the dimensions of exposure in relation to the domains of competency use. Network analyses showed that, among the three exposure domains, exposure to suicidal communication was most prominent. On the clergy competency use side, pastoral care for a suicidal person demonstrated the strongest centrality. Integrating structured suicide prevention training with pastoral experience is therefore important for ensuring consistent and effective responses to individuals at risk.